1999
DOI: 10.1046/j.1525-1594.1999.06282.x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Postoperative Percutaneous Cardiopulmonary Support Using a Centrifugal Pump: Retrospective Analysis of Complications

Abstract: Between January 1992 and December 1997, we employed percutaneous cardiopulmonary support (PCPS) using a centrifugal pump in 25 patients. In 21 of them, PCPS was used postcardiotomy. These patients could not be weaned from cardiopulmonary bypass due to profound ventricular failure. As for the other 4 patients, PCPS was used preoperatively for profound cardiogenic shock, a thrombosed valve, a stuck valve, and pulmonary embolization. Nine patients (43%) were weaned from PCPS (Group 1), and 3 (14%) were discharged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…The other factors, aortic cross‐clamp time and preoperative cardiac function, that were significant for weaning from PCPS were not significant for hospital mortality. Bleeding during mechanical support is the most frequent complication (11,14) and massive bleeding results in hypovolemia, which in turn causes unstable hemodynamics due to the impaired inflow volume of PCPS; however, factors related to bleeding (re‐exploration and pRBC/FFP transfusion) were not statistically significant in our series. In this study, urine output during the initial 24 h after the institution of PCPS was much higher for hospital survivors than for hospital nonsurvivors.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The other factors, aortic cross‐clamp time and preoperative cardiac function, that were significant for weaning from PCPS were not significant for hospital mortality. Bleeding during mechanical support is the most frequent complication (11,14) and massive bleeding results in hypovolemia, which in turn causes unstable hemodynamics due to the impaired inflow volume of PCPS; however, factors related to bleeding (re‐exploration and pRBC/FFP transfusion) were not statistically significant in our series. In this study, urine output during the initial 24 h after the institution of PCPS was much higher for hospital survivors than for hospital nonsurvivors.…”
Section: Discussionmentioning
confidence: 53%
“…Although this system is beneficial for maintaining hemodynamic status and visceral perfusion during circulatory collapse and for reducing the right ventricular preload, the indication of PCPS has not achieved worldwide acceptance, especially for postcardiotomy LOS. Moreover, the weaning rates for PCPS and the survival rates vary because of the variety of underlying diseases, and it has been suggested that one of the major factors related to survival is the ability to correct the underlying pathology (3,4,11). Thus, its elective use for patients undergoing high‐risk coronary intervention has demonstrated acceptable results (2,5), though the clinical use of postcardiotomy LOS has been reported to be unsatisfactory, with survival rates ranging from 4% to 30% (3,6–12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Percutaneous cardiopulmonary support with a centrifugal pump has been widely utilized in patients with acute cardiac failure, but the mean duration of assist per pump was only 2.2-3.8 days (12)(13)(14). Mean successful pump use for ECLS was 10.5 ± 7.2 days, without any major clinical complications.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Alternate support from ventricular assist devices is necessary when cardiac function does not recover and powerful long-term assistance is needed. 7,8 PCPS provides immediate life-sustaining circulatory and oxygenation support until diagnostic and therapeutic interventions can be initiated.…”
Section: Discussionmentioning
confidence: 99%